A Mini-Review On The Fabrication Of Expanded Graphite And Its Metal Oxide Composites For The Photodegradation Of Dyes (Journal of the College of Basic Education, 2025)
This mini review provides an overview of methods for manufacturing expanded graphite (EGT) and the use of its composites with metal oxides in the field of photodegradation of dyes. Dyes from textile manufacturing represent a significant environmental pollution problem in waterways worldwide, highlighting the need for environmentally friendly and efficient technologies to remove dyes from industrial and local wastewater. Photodegradation technologies offer a low-cost, sustainable solution with minimal secondary pollution. Carbon-based materials, such as expanded graphite, are advantageous in enhancing catalytic activity. Accordingly, this review will explore the different fabrication techniques of expanded graphite and summarize the recent development of EGT-metal oxide composite in photocatalysis process towards environmental remediation application. From this study concludes that the photodegradation method using metal oxide-expanded graphite composite is an effective and cost-efficient option for degrading dyes.